PERBANDINGAN KINERJA BANK KONVENSIONAL DAN BANK SYARIAH DI INDONESIA - Achmarul Fajar; Bunga Mawar Mira; Rysca Alvia; Adinda Nabilla Abdilla Putri; Lutfiadi (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze and compare the performance of conventional and Islamic banks in Indonesia and identify the factors influencing their similarities and differences. This study employs a qualitative approach with a descriptive-comparative research design. Secondary data were collected through documentation and library research, including annual reports, financial statements, national banking statistics, official institutional reports, books, scientific journals, articles, and previous studies. The analysis was conducted by comparing indicators of profitability, operational efficiency, liquidity, credit or financing quality, and capital adequacy. The results show that conventional banks have advantages in terms of business scale, service networks, customer base, product variety, and risk management experience. Meanwhile, Islamic banks have advantages in applying the principles of fairness, risk sharing, diverse contracts, and compliance with Sharia principles. Differences in the performance of the two types of banks are influenced by operational principles and business models, business scale, market share, public trust, financial literacy and inclusion, technology utilization, human resource quality, regulations, and macroeconomic conditions. Although conventional banks continue to dominate the national banking industry, Islamic banks have significant growth opportunities through institutional strengthening, product innovation, improved financial literacy, and digital transformation. Both banking systems have positive prospects and complementary roles in supporting national economic stability and growth.